SMOOTH : a system for mobility training at home for people with Parkinson's Disease - Muras, Joanna A. (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2010)
Assistive technology has the capacity provide to people with limitations the opportunity to improve their quality of life and increase their independence in daily living. The promise of emerging pervasive computing technologies is that they will enable a new generation of assistive technologies to offer individuals the opportunity to stay in their homes for longer and manage everyday tasks without placing a significant burden on their caregivers.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin.